Blessed are the cheesemakers eaudiobook - Lynch, Sarah-Kate (HighBridge Audio, 2003)
Set mainly in Ireland on a dairy farm, Blessed Are the Cheesemakers tells the story of two old men, Joseph "Corrie" Corrigan and Joseph "Fee" Feehan who are the best cheesemakers in the world, and the broken hearted women and whisky-soaked men they rescue in the course of their daily doing. There's a love story, a family story, the lore of cheese-making (fiction or not), and some wonderfully appealing characters, including the cows which only give their top grade product when milked by vegetarian, unwed, pregnant teenagers who sing "The Sound of Music" while at their task. A tender and funny novel with a colorful cast of characters.